Analysis of electrochemical and liver microsomal transformation products of lasalocid by LC/HRMS. (27th July 2022) - Knoche, Lisa; Lisec, Jan; Koch, Matthias
Abstract : Rationale: Lasalocid (LAS), an ionophore, is used in cattle and poultry farming as feed additive for its antibiotic and growth‐promoting properties. Literature on transformation products (TP) resulting from LAS degradation is limited. So far, only hydroxylation is found to occur as the metabolic reaction during the LAS degradation. To investigate potential TPs of LAS, we used electrochemistry (EC) and liver microsome (LM) assays to synthesize TPs, which were identified using liquid chromatography high‐resolution mass spectrometry (LC/HRMS). Methods: Electrochemically produced TPs were analyzed online by direct coupling of the electrochemical cell to the electrospray ionization (ESI) source of a Sciex Triple‐TOF high resolution mass spectrometer. Then, EC‐treated LAS solution was collected and analyzed offline using LC/HRMS to confirm stable TPs and improve their annotation with a chemical structure due to informative MS/MS spectra. In a complementary approach, TPs formed by rat and human microsomal incubation were investigated using LC/HRMS. The resulting data were used to investigate LAS modification reactions and elucidate the chemical structure of obtained TPs. Results: The online measurements identified a broad variety of TPs, resulting from modification reactions like (de‐)hydrogenation, hydration, methylation, oxidation as well as adduct formation with methanol. We consistently observed different ion complexations of LAS and LAS‐TPs (Na + ; 2Na + K + ; NaNH4 + ; KNH4 + ). Two stable methylated EC‐TPs were found, structurally annotated, and assigned to a likely modification reaction. Using LM incubation, seven TPs were formed, mostly by oxidation/hydroxylation. After the identification of LM‐TPs as Na + ‐complexes, we identified LM‐TPs as K + ‐complexes. Conclusion: We identified and characterized TPs of LAS using EC‐ and LM‐based methods. Moreover, we found different ion complexes of LAS‐based TPs. This knowledge, especially the different ion complexes, may help elucidate the metabolic and environmental degradation pathways of LAS.